A pathway to cyclic carbonates: Cycloaddition of carbon dioxide to epoxidized methyl oleate on grafted heterogeneous catalysts - Wander Y. Perez-Sena; Fabrizio Ciccarelli; Kari Eränen; Martino Di Serio; Vincenzo Russo; Tapio Salmi (Journal of CO2 Utilization)
The conversion of CO2 into value-added cyclic carbonates via cycloaddition to bio-derived epoxides presents a sustainable approach for CO2 utilization. However, the production of cyclic carbonates from bio-sources such as epoxidized vegetable oils (EVOs) have significant challenges due to the low reactivity of CO2 and the steric hindrance of internal epoxides in these bulky substrates. Consequently, the majority of systems for CO2 fixation to bio-based epoxides rely on homogeneous catalysis. This study investigated the conversion of epoxidized methyl oleate, a model compound for EVOs, into its corresponding cyclic carbonate using heterogeneous 4-pyrrolidinopyridine-based catalysts. The influence of various catalytic parameters, such as the halide counter anions (Cl, Br, I) and incorporated metal Lewis acid centra, was explored within the catalyst. Among the halide counter anions, bromide exhibited a superior performance, achieving 65 % conversion and 59 % cyclic carbonate yield by the end of the experiment, while the effect of various metal centra was less pronounced, with an overall improvement in the cyclic carbonate yield of less than 10 % compared to the metal-free catalyst. A comprehensive study of reaction parameters, including the temperature (100–170°C), the CO2 pressure (20–40 bar), and the catalyst loading (2.9–10.7 wt%), was conducted in a laboratory-scale autoclave reactor to elucidate the behavior of the reaction system.